A broadband and high‐gain differentially fed suspended plate antenna integrated with solar cells. Issue 9 (12th May 2022) - Lai, Jingyu; Luo, Yu; Yan, Ningning; An, Wenxing; Ma, Kaixue
Abstract: This paper proposes a differentially fed suspended plate antenna (SPA) integrated with solar cells. A structure of hollow cylinders is used to support the patch and enhance the gain by suppressing any unwanted high‐order mode. More importantly, the cathode of the solar cells is connected to the antenna ground to improve the compatibility of the antenna and solar cells without introducing additional filters. Differentially fed l ‐shaped coaxial probes feed the SPA to enhance the bandwidth. The anode and the cathode of the two solar cells are connected and located directly above the patch. A prototype of the solar cell SPA is fabricated and measured to verify the stability of its radiation and energy‐harvesting performance. The measurement results show that the bandwidth of the proposed solar cell SPA is 3.2–5.1 GHz for wideband application, and its gain is higher than 9.51 dBi in the operating band.